Effect of the 24 September 2011 solar radio burst on precise point positioning service - Sreeja, V.; Aquino, M.; de Jong, Kees; Visser, Hans (American Geophysical Union, 2014)
An intense solar radio burst occurred on 24 September 2011, which affected the tracking of Global Navigation Satellite Systems’ (GNSS) signals by receivers located in the sunlit hemisphere of the Earth. This manuscript presents for the first time the impacts of this radio burst on the availability of Fugro’s real-time precise point positioning service for GNSS receivers and on the quality of the L band data link used to broadcast this service. During the peak of the radio burst (12:50–13:20 UT), a reduction in the L band signal-to-noise ratio (SNR) is observed. For some receiver locations, a reset in the position filter is observed, which can be either due to the reduction in the L band SNR or the reduction in the number of tracked GNSS satellites. This reset in the position filter is accompanied by degradation in the positioning accuracy, which is also discussed herein.